Body composition isokinetic knee extensor strength and balance as predictors of competition performance in junior weightlifters - Ulupinar, S.; Özbay, S. (Isokinetics and Exercise Science, 2020)
Although it is known that isokinetic knee extensor strength and balance ability are important, valid and reliable parameters, they have not been used hitherto to predict the performance of young weightlifters. OBJECTIVE: To investigate the relationship between body composition, isokinetic knee extensor strength, balance, and weightlifting performance and to determine whether these factors predict competition performance in junior men weightlifters. METHODS: Fifty-one male junior weightlifters (age: 15.9 ± 1.2 years, height: 161.9 ± 7.7 cm, body mass: 62.7 ± 11.3 kg) participated in this study. Participants performed isokinetic knee extensor strength tests in concentric mode (at 60 and 180 ° /s) and balance tests (static and dynamic). Competition performance was calculated according to the Sinclair equation, which was used as the dependent variable in the statistical analysis. The extent to which the independent variables predicted competition performance was determined by bivariate correlations and multiple linear regression analysis. RESULTS: Significant correlations were found between the Sinclair score and the independent variables (r = 0.496-0.804, p < 0.05). Three models were fitted by hierarchical linear regression analysis. Body fat percentage was determined as a control variable in step one, isokinetic knee extensor strength at 180 ° /s was included in step two, and static balance was included in step three, with all three contributing to the models significantly (p = 0.0001, p = 0.0001, and p = 0.003, respectively). The variance of competition performance was explained by approximately 65% in step one, approximately 78% in step two, and approximately 82% in step three. CONCLUSIONS: The results of this study suggest that isokinetic knee extensor strength, static balance, and body fat percentage are effective for predicting competition performance in junior weightlifters.